EKONOMIKALÍQ PÁNLERDI OQÍTÍWDA INTERAKTIV METODLARDAN PAYDALANÍWDÍŃ ÓZGESHELIGI (Ulıwma orta bilim beriw mektepleri mısalında) - Tolepov, E.T. (SCIENCE and SOCIETY, 2025)
The article will focus on interactive methods that can be used in economics lessons.The interactive method is used to activate the assimilation of knowledge by students, the development of personal qualities by increasing the activity between students and the teacher in the learning process.